'I Think the Carer-Partner Dichotomy is Always Interesting': Tensions in Health Professionals' Engagement with Spousal Care givers of People with Parkinson's. Issue 2 (11th March 2016) - Bolland, Meredith; Guilfoyle, Andrew; Bucks, Romola S.
Abstract : Background: The spousal care givers of people with Parkinson's (PwP) have unique, first-hand information that is invaluable in the effective management of Parkinson's disease (PD). However, there is a dearth of research that specifically focuses on health professionals' experiences of engagement with the spousal care givers of PwP. Methods: Interpretative phenomenological analysis (IPA) was used to describe and identify the meaning that health professionals working with PD (HPPs) gave to their engagement experiences with spousal care givers of PwP. Semi-structured interviews with a purposive sample of 12 HPPs were digitally recorded, transcribed verbatim and analysed for emerging themes. Results: Two major themes emerged from the interviews with HPPs: (i) the Philosophy of Care (PoC) is an Intrinsic Element in the Engagement Experience; and (ii) HPPs Expressed a Deep Appreciation of Partners' Support of the PwP. HPPs experienced significant tensions and challenges in their engagements with the partners of PwP, as a result of the interaction between their lived reality and their PoC. They also appreciated greatly the caregiving provided by the partners. The insights gained have the potential to ease or resolve problematic tensions within the engagement process.